Quantifying the effect of age on passive range of motion of the cervical spine in healthy working-age women - Salo, Petri K; Häkkinen, Arja H; Kautiainen, Hannu; Ylinen, Jari J (The journal of orthopaedic and sports physical therapy, 2009)
Cross-sectional study. To assess age-related changes and determine reference values for passive range of motion of the cervical spine in healthy women of working age. Although cervical mobility is age dependent, the amount in which aging affects passive range of motion has not been previously reported. It is clinically important to know the effect of normal aging process on cervical motion to be able to separate and evaluate the possible effect of pathological processes. Two hundred twenty healthy women, aged 20 to 59 years, participated in the study. Passive range of motion of the cervical spine in flexion, extension, lateral flexion, and axial rotation was measured with the Cervical Measurement System. Measurements to calculate intrarater reliability were obtained on 22 subjects. Passive range of motion of the cervical spine diminished linearly with increasing age in all measured movement planes (P<.001 for all movements except for flexion which was P = .018). Mean body mass index adjusted reduction in passive range of motion was 0.5 degrees per 1-year increase in age. Intraclass correlation coefficients for intrarater reliability ranged from 0.79 to 0.92. A gradual age-related reduction in passive cervical range of motion was observed in women of working age.